Pola Transmisi Pengetahuan Seniman Tradisi dalam Regenerasi Kesenian Kethek Ogleng di Kabupaten Wonogiri - Iyok Andriyanto; Fawarti Gendra Nata Utami (Jurnal Ilmu Sosial dan Humaniora, 2026)
Kethek Ogleng is a traditional performing art form that has developed in Wonogiri Regency and holds strong historical and cultural value. The sustainability of this art form depends heavily on the regeneration process of artists, which occurs through the transmission of knowledge between generations. This study aims to examine the transmission patterns of knowledge carried out by traditional artists in their efforts to regenerate Kethek Ogleng in Wonogiri Regency. The research method used was qualitative with a descriptive-analytical approach. Data collection techniques included observation, in-depth interviews with artists, trainers, and the next generation, and documentation. The results indicate that the transmission pattern of Kethek Ogleng knowledge occurs informally through direct learning, role models, and repeated practice within the family environment and art studios. Furthermore, the transmission process is also influenced by the role of the community, local cultural values, and support from the surrounding community. This study concludes that traditional and community-based knowledge transmission patterns are key factors in fostering the emergence and regeneration of Kethek Ogleng in Wonogiri Regency.